The global drought-sensitive areas will expand in the future - Qiaoqiao Li; Aizhong Ye; Reshmita Nath; Yuhang Zhang; Junju Zhou (Ecological Indicators, 2025)
Climate change and human activities are intensifying drought conditions, significantly altering drought propagation processes. However, these changes remain insufficiently understood, particularly for typical drought partitions such as humid, drought-sensitive, and arid types of drought propagation partition. Therefore, this study examines the change on these partitions under three Shared Socioeconomic Pathways (SSP1-2.6, SSP3-7.0, and SSP5-8.5) to elucidate global drought trends. The results show that the global drought-sensitive area will expand by 1.89 × 106 km2, which is roughly the size of Sudan (1.88 × 106 km2). Notably, in South America alone, the drought-sensitive area is projected to increase by 1.27 × 106 km2, equivalent to the size of Niger. While in South America the humid partition will shrink by 1.45 × 106 km2, with nearly 60 % transitioning into drought-sensitive areas. Overall, human activities are expected to drive drought partitions in an unfavorable direction, with approximately 3.26 × 106 km2 will shift from humid-type partition to drought-sensitive areas or from drought-sensitive areas to arid-type partitions under the SSP5-8.5 scenario, similar to the size of India (3.29 × 106 km2). Among all the climate zones, the changes are most notable in the humid and semi-arid regions. Significant transformations in drought propagation patterns are evident in the Great Plains of the United States of America, southern and central Europe, and the Amazon basin in South America, where declining precipitation and intensifying land–atmosphere coupling are the main driving factors. These findings provide critical insights for drought prediction and management in the context of climate change.